The Effect of leaves Feeding with Heomic Acid in Some Growth and Producing Properties of Sun Flower Plant. Helianthus annuus L - Al-Shamry, Ali Mutashar Marza; Al-Zubaidi, Najim Abdullah Juma (Journal of agricultural, environmental and veterinary sciences, 2017)
A factorial experiment was applied according to Randomized Complete Block Design (R.C.B.D) with three replications, during the spring season 2017 in Diyala / Baquba / Buhriz city, using silt loam soil to study the effect of four levels of foliar fertilization with humic acid 0, 2, 4, 6 ml.L-1 in the growth and yield of sunflower, Helianthus annuus  L. (LuLeo). The results showed significant differences for level of humic acid 6 ml.L-1 in plant height which gave an average 213.73 cm, leaf area of the plant 5597.32 cm2, chlorophyll index 48.64 SPAD, dry weight of the plant 215.0 g, number of seeds in the flowery disc 1494 seed.disc-1, 1000 seeds weight 88.3 g, plant yield 127.91 g.plant-1, total yield 6.81 ton.h-1 and oil percentage in the seeds 43.184%, while the level 4 ml.L-1 humic acid gave the highest average for the protein percentage in the seeds 18.34%.
Keywords: The effect; Sunflower; Humic acid; Foliar nutrition; Growth characters; Yield characters